2020
DOI: 10.1108/et-03-2019-0053
|View full text |Cite
|
Sign up to set email alerts
|

Do intentions ever die? The temporal stability of entrepreneurial intention and link to behavior

Abstract: PurposeThis study aims to contribute to entrepreneurial intention research by examining the theory of planned behavior model in a longitudinal follow-up of the same individuals from a point at which they were studying until six to eight years after graduation and the link between entrepreneurial intention and actual behavior. The objectives of the paper are as follows: to examine the development and temporal stability of entrepreneurial intention and to examine the link between entrepreneurial intention and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
0
37
0
1
Order By: Relevance
“…Students, as agents of power, can be selective in interpreting and assimilating information that is most relevant for them (Kyrö, 2015). The teacher, as a social actor, becomes a support for collective learning by trying to establish a conducive context for its occurrence (Joensuu-Salo et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Students, as agents of power, can be selective in interpreting and assimilating information that is most relevant for them (Kyrö, 2015). The teacher, as a social actor, becomes a support for collective learning by trying to establish a conducive context for its occurrence (Joensuu-Salo et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this case it should be noted that extrinsic motivation was implemented as a construct in direct opposition to intrinsic motivation and this does not align with the reasoning of SDT, according to which it can vary in the extent of its autonomy (Taylor et al, 2014). A key influence of Hytti et al’s study (2010) was the requirement for us as educators to avoid preconceptions about student motivation while it also provided us with the encouragement to experiment with new methods that could better satisfy a plurality of needs (Joensuu-Salo et al, 2020). It is believed that, in doing so, we have more opportunities to appeal to higher-quality motivational types (those more associated with identification, integration and intrinsic regulation), which have been shown to benefit from a greater likelihood of producing positive outcomes such as increases in self-esteem, learning, interest and even academic performance (Mageau and Vallerand, 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Entrepreneurial intention is quite dynamic and has the power to predict actual entrepreneurial behavior (Fayolle and Linan, 2014;Kautonen et al, 2015;Ligouri et al, 2018). Meanwhile, Linan et al (2011) and Joensuu-Salo et al (2020), in longitudinal studies, found that entrepreneurial intention is stable over time, hence proves its strength to predict subsequent behaviour and even alter previous behaviour tendencies. This is in consonance with Krueger et al (2000, p. 411) who stated that "intentions have proven the best predictor of planned behavior, particularly when that behavior is rare, hard to observe, or involves unpredictable time lags".…”
Section: Introductionmentioning
confidence: 99%